Emerging evidence linking the gut microbiome to neurologic disorders - Jessica A. Griffiths; Sarkis K. Mazmanian (Genome Medicine, 2018)
Editorial summary The gut microbiome contributes to the development and function of the immune, metabolic, and nervous systems. Furthermore, commensal bacteria modulate symptoms and pathology in mouse models of neuropsychiatric and neurodevelopmental diseases. Uncovering mechanisms that are utilized by the microbiome to mediate gut–brain connections may provide novel opportunities to target therapies to the gut in order to treat neurologic disorders.